Time for the ephemeral. an anotation on contemporary artistic practice and urban space. (2007)
Routes across urban spaces describe the transit of thetales and descriptions we make. Far from subordinatingephemeral artistic practices to urban spaces, or subordinatingspaces to the role of stages, this article offersan integrated reading of unstable spaces and transitoryephemeral actions in Bogotá.